Report on research, innovation and technological performance in Germany 2021 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2021)
[Foreword ...] Chapter A 1 is dedicated to the impact of the COVID-19 crisis on the innovation activities of companies. For the majority of German companies, the current crisis situation negatively affects ongoing or planned innovation projects. In the Commission of Experts' opinion, the crisis can also act as a catalyst for the transition to new technologies and thus improve Germany's long-term competitiveness. This assumes that economic stimulus programmes and growth policy measures are designed with R&I in mind. In chapter A 2, the Commission of Experts comments on the Federal Government's research and innovation policy measures of the past year. It appreciates that the establishment of the Future Fund improves the financial framework conditions for the provision of venture and growth capital. It also welcomes the promotion of future technologies such as hydrogen and quantum technology within the framework of the Future Package. At the same time, it suggests accompanying measures to increase the effectiveness of key R&I policy initiatives launched in 2020. Although overcoming the COVID-19 crisis will be a key task for the new Federal Government in the coming legislative period, R&I policy must continue to be prioritized. In chapter A 3, the Commission of Experts names five priorities that should guide R&I policy in the next legislative period. These are: 'Addressing Grand Societal Challenges', 'Catching Up and Avoiding Technological Gaps', 'Securing the Skilled Labour Base', 'Increasing Innovation Participation', and 'Increasing the Agility of R&I Policy'. R&I policy has the responsibility to contribute to addressing the grand societal challenges and to initiate transformative change. As the policy approach of New Mission Orientation supports this, the Commission of Experts advocates in chapter B 1 that the Federal Government should give greater attention to this policy approach in a marketoriented version. The successful implementation of New Mission Orientation requires agile policy making. The Commission of Experts welcomes that R&I policy has already become more agile in recent years but calls on the Federal Government to incorporate agility in political action even more systematically. In chapter B 2, the Commission of Experts analyses how the system of vocational and continuing education and training (VET/CET) must change to keep pace with changing competence requirements due to digital transformation. To secure employment and realize innovation potentials, it is necessary to adapt VET to the requirements of the digitalized world of work and to strengthen job-related CET. The Commission of Experts recommends strengthening occupational adaptability by expanding flexible additional qualifications, providing sufficient resources for higher-quality CET programmes, and additionally promoting preventive adaptation qualifications. It moreover welcomes initiatives for the comprehensive monitoring of occupational skills in support of more tailored VET/CET. In chapter B 3, the Commission of Experts looks at the gene scissors CRISPR/Cas, a new tool for gene editing, and its use for medical purposes. Measured by the number of publications, Germany occupies a good position in CRISPR/Cas research in an international comparison. However, Germany falls behind when key performance indicators in the application and commercialization of this technology are considered. To be able to exploit untapped potential in the translation of research results into application, the framework conditions for approval procedures and the provision of private venture and growth capital must be improved and interdisciplinary cooperation and working groups must be promoted.
Keywords: 330